1986
DOI: 10.1136/oem.43.9.615
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of ethoxyacetic acid after experimental human exposure to ethylene glycol monoethyl ether.

Abstract: Ten healthy male subjects were exposed to ethylene glycol monoethyl ether (EGEE) under various conditions of exposure concentration and physical workload and their urinary excretion of ethoxyacetic acid was followed up for 42 hours. Maximal excretion of ethoxyacetic acid was reached three to four hours after the end of the four hour exposure period. Afterwards, ethoxyacetic acid excretion declined slowly with a biological half life of 21-24 hours. Ethoxyacetic acid excretion increased as the uptake of EGEE inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
1
22
0
3
Order By: Relevance
“…This field study on a gro up of five women da ily exposed to a mixture of EGEE and EGEE-Ac confirms the conclusions fro m our short-term experiments regarding the relatively long biological hal f-time of the main metabolite etho xyacetic acid and the expected accumu lation effect (6,7). From these experiments with single 4-h expos ure periods, a half-time of 21-24 h was estimated.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This field study on a gro up of five women da ily exposed to a mixture of EGEE and EGEE-Ac confirms the conclusions fro m our short-term experiments regarding the relatively long biological hal f-time of the main metabolite etho xyacetic acid and the expected accumu lation effect (6,7). From these experiments with single 4-h expos ure periods, a half-time of 21-24 h was estimated.…”
Section: Discussionsupporting
confidence: 69%
“…Sur veys on occupa tional exposures to these solvents and hu man epidemiologic findings are still scarce. Recently we studied the urinary excretion of ethoxyacetic acid after short-ter m (4 h) experimenta l exposures of volunteers to the ethyl ether of ethylene glycol (EGEE) and the eth yl ether of ethylene glycol acetat e (EG EE-Ac) (6,7). We established that ethox yacetic acid could be used as a specific and sensitiv e biological expos ure parameter for bo th products .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent paper also showed that subjects recovered very quickly from the 2-ME-induced hematological effects as the airborne concentrations of 2-ME and its major toxic metabolite, MAA (2-methoxy acetic acid), were reduced 35,36) . Since the half-life of MAA in humans (77-100 h) [37][38][39] is much longer than that of EAA (23-42 h) 40,41) , we speculate that the toxic metabolite, EAA, stays in humans a shorter time than MAA, and human subjects can recover more quickly from the 2-EEA-induced hematological effects than those induced by 2-ME. Since increasing temporal trends of hemoglobin, haematocrit, and the RBC count were found in this study for the exposed workers during the followup period, these findings suggest that reducing exposures through dermal contact can lead to the gradual amelioration of the hematological effects in 2-EEAexposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Die Halbwertszeiten werden in der Literatur mit Werten zwischen 21 und 42 Stunden angegeben (22,18,21,25 (22,18,21).…”
Section: Metabolismus Und Kinetikunclassified